Effective Environmental Factors on Milk Composition, Rennet Coagulation Time and Urea Content of in Anatolian Buffaloes Milk of Ilıkpınar Village Hatay Province - Sekerden, Özel; Avsar, Yahya Kemal (Journal of Buffalo Science, 2014)
The objectives of this study were to investigate determining environmental factors on composition, renneting time, urea concentration, acidity, density and pH of Anatolian Buffaloes milk. As a total of 115 milk samples from 53 cows that were calved in the period of 2004 and 2005 years in 8 units of Ilıkpınar Village were collected in morning milkings in June, September, December and March. The cows were at their lactation days 30±15, 60±15, 90±15, 120±15, 150±15, 180±15, 210±15, 240±15 and 270±15. The milk samples were analysed for total dry matter, fat, protein, ash, density, pH, acidity, renneting time and urea content. Rennet coagulation time, urea, protein and fat contents were determined using Berridge, photometric, formal titration and Gerber methods, respectively. Data were classified as follows; lactation stages: 1 (30±15, 60±15, 90±15 days): 2 (120±15, 150±15, 180±15): 3 (210±15, 240±15, 270±15); calving year: 1 (2004), 2 (2005); calving season: 1 (January-May), 2 (September and October); month of samples collection: 1 (June), 2 (September), 3 (December), 4 (March); lactation order: 1 and 2 : 1, 3 and 4: 2, 5 and 6: 3. The effects of environmental factors of each variable were investigated separately and analysed using analysis of variance. Production mount in all the characteristics; calving year and lactation stage in most of the characteristics; lactation order on fat and protein contents; unit and calving season in some of the characteristics were found to be effective significantly. SPSS program was used in the statistical procedures.